Distance Matrices and Isometric Embeddings - Bogomolny, E.; Bohigas, O.; Schmit, C. (Журнал математичної фізики, аналізу, геометрії, 2008)
We review the relations between distance matrices and isometric embeddings and give simple proofs that distance matrices defined on euclidean and spherical spaces have all eigenvalues except one nonpositive. Several generalizations are discussed.Mathematics Subject Classification: 15A52, 82B41.